Cyber chain management - Hackney, Ray; Burn, Janice (Business process management journal, 2004)
This position paper revisits earlier research to outline contemporary thinking on the nature of cyber-marketing strategies and the implications for organisations in the post-Net era. It identifies in particular recent frameworks which appear to offer insights into the complexities and uncertainties associated with critical channels and new media for proactive marketing approaches. The emphasis within the paper is on the effective implementation of strategies driven by electronic networks generated through the Internet. An important contribution therefore is to recognise the dynamics of global.